Spousal religious conversion: Choice of laws and forums in Malaysia - Shuaib, Farid Sufian (International Islamic University Malaysia, 2011)
Malaysia has a multi-court system where civil courts, Shariah courts and Native courts running parallel to one another. This is produced by the diversity in her population in terms of religion, race and custom. These different court systems most of the time run independent of one another since subject matters and parties before the courts are different. However, in isolated cases, conflict may occur between these courts when on the face of it different court systems have jurisdiction over the same parties involving the same issues. This occurs for instance where a spouse from a non-Muslim marriage converts to Islam. In such a case questions may arise as to which court would be the right court possessing jurisdiction over the marriage in dissolving the marriage if necessary and in providing ancillary relief such as a maintenance order and custody of children. Resolution on jurisdiction of the courts in this case is important to ensure a fair settlement for the parties.